Sexual Dimorphism From Third Cervical Vertebra (c3) On Lateral Cervical Radiograph: A 2-dimensional Geometric Morphometric Approach - Muhammad Faiz Mohd Fauad; Aspalilah Alias; Ker Woon Choy; Wei Lin Ng; Eric Chung; Yuan Seng Wu; Ku Mastura Ku Mohd Noor (Elsevier, 2024)
Indexed by WOS/ Scopus